Implementation of SiTabur: A Simple Fertilizer Spreading System for Enhancing Efficiency and Productivity in Penanggungan Village, Banjarnegara - Sausan Abdullah; Nur Khamidah; Adeliya Pertama Sari; Rohma Ainal Marwa; Agi Setiawan Widyatmoko; Yanuar Alkindy Mudhopir; Anggita Wulandari; Tegar Adit Saputra; Isna Firdatul Hilma; Maritza Yuliviana; Arif Budiman; Alfato Yusnar Kharismasyah (Proceedings Series on Social Sciences & Humanities, 2025)
Farmers' technological utilization has a significant impact on agricultural output. Most chile and cabbage growers in Penanggungan Village, Wanayasa District, Banjarnegara Regency, still hand-spread fertilizer. This method is time-consuming, involves a lot of energy, and has the potential to cause health issues including back pain. The team used the Community Service Program (KKN) to conduct outreach and training efforts for the creation of SiTabur (a simple fertilizer spreading tool) as an example of appropriate technology that is inexpensive, simple to create, and can be operated directly by farmers. This instrument is made of PVC pipe and has a simple mechanism for adjusting the fertilizer dose to the plant's demands. Outreach, assembly training, and tool demonstrations on locals' agricultural land are all used to carry out activities. According to the evaluation results, farmers' understanding and skills in making and utilizing the tool improved. Farmers replied positively since SiTabur has been shown to assist save time, minimize physical load, and improve fertilization efficiency. Farmers should be able to produce this instrument on their own in the future to ensure the long-term viability of more productive farming techniques